A contested Caribbean indigeneity : language, social practice, and identity within Puerto Rico Taíno activism - Feliciano-Santos, Sherina (New Brunswick, NJ : Rutgers University Press, 2021)
"A Contested Caribbean Indigeneity is an in-depth analysis of the debates surrounding Taíno/Boricua activism in Puerto Rico and the Caribbean diaspora in New York City. Drawing on in-depth ethnographic research, media analysis, and historical documents, the book explores the varied experiences and motivations of Taíno/Boricua activists as well as the alternative fonts of authority they draw on to claim what is commonly thought to be an extinct ethnic category. It explores the historical and interactional challenges involved in claiming membership in, what for many Puerto Ricans, is an impossible affiliation. In focusing on Taíno/Boricua activism, the books aims to identify a critical space from which to analyze and decolonize ethnoracial ideologies of Puerto Ricanness, issues of class and education, Puerto Rican nationalisms and colonialisms, as well as important questions regarding narrative, historical memory, and belonging"--
Part 1. Competing historical narratives regarding Taíno extinction -- The stakes of being Taíno -- Historical discourses and debates about Puerto Rico's indigenous trajectory -- Part 2. The Puerto Rican nation and ethnoracial regimes in Puerto Rico -- Jíbaros and jibaridades, ambiguities and possiblities -- Impossible identities -- Part 3. Taíno heritage and political mobilization -- (Re)Constructing heritage, narratives of linguistic belonging -- How do you see the world as a Taíno? : Conceptualizing the Taíno -- Protest, surveillance, and cermony -- Conclusion.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Taino Indians -- Puerto Rico -- Ethnic identity; Taino Indians -- Political activity -- Puerto Rico; National characteristics, Puerto Rican; Jíbaro (Puerto Rican identity); Indian activists -- Puerto Rico; Ethnicity -- Puerto Rico; Puerto Ricans; Taïno -- Identité ethnique -- Porto Rico; Taïno -- Activité politique -- Porto Rico; Portoricains; Jibaro (Identité portoricaine); Activistes des Peuples autochtones -- Porto Rico; Ethnicité -- Porto Rico; Puerto Ricans; Ethnicity; Indian activists; Jíbaro (Puerto Rican identity); National characteristics, Puerto Rican; Puerto Rico